Molecular and Biological Characterization of Ralstonia Phage RsoM1USA, a New Species of P2virus, Isolated in the United States - Addy, Hardian Susilo; Ahmad, Abdelmonim Ali; Huang, Qi (Frontiers in Microbiology, 2019)
The first Ralstonia-infecting bacteriophage from soil of the USA, designated RsoM1USA, was isolated from a tomato field in Florida. Electron Microscopy revealed that phage RsoM1USA is member of the genus P2virus in the family Myoviridae with an icosahedral head of about 66 nm in diameter, a contractile tail of about 152 nm in length, and a long “neck”. Phage RsoM1USA has a relatively wide host range infecting 13 of the 30 tested R. solanacearum species complex strains collected worldwide in each of the three Ralstonia species: R. solanacearum, R. pseudosolanacearum and R. syzygii. The phage completed its infection cycle 180 minutes post infection with a burst size of about 56 particles per cell. Phage RsoM1USA has a genome of 39,309 nucleotides containing 58 open reading frames (ORFs) and is closely related to Ralstonia phage RSA1, the type phage of the species Ralstonia virus RSA1. The genomic organization of phage RsoM1USA is also similar to that of phage RSA1, but their integrases share no sequence homology. In addition, we determined that the integration of phage RsoM1USA into its susceptible R. solanacearum strain K60 is mediated by the 3’ 45-base portion of the threonine tRNA (TGT), not arginine tRNA (CCG) as reported for phage RSA1, confirming that the two phages use different mechanism for integration. Our proteomic analysis of the purified virions supported the annotation of the main structural proteins. Infection of a susceptible R. solanacearum strain RUN302 by phage RsoM1USA resulted in significantly reduced growth of the infected bacterium in vitro, but not virulence in tomato plants, as compared to its uninfected RUN302 strain. Due to its differences from phage RSA1, phage RsoM1USA should be considered the type phage of a new species with a proposed species name of Ralstonia virus RsoM1USA.